Impact of the pericapsular nerve group (PENG) block on postoperative analgesia and functional recovery following total hip arthroplasty: a randomised, observer‐masked, controlled trial. (1st July 2021) - Pascarella, G.; Costa, F.; Del Buono, R.; Pulitanò, R.; Strumia, A.; Piliego, C.; De Quattro, E.; Cataldo, R.; Agrò, F. E.; Carassiti, M.; ,
Summary: The pericapsular nerve group (PENG) block is a novel regional anaesthesia technique that aims to provide hip analgesia with preservation of motor function, although evidence is currently lacking. In this single‐centre, observer‐masked, randomised controlled trial, patients undergoing total hip arthroplasty received pericapsular nerve group block or no block (control group). Primary outcome measure was maximum pain scores (0–10 numeric rating scale) measured in the first 48 h after surgery. Secondary outcomes included postoperative opioid consumption; patient mobilisation assessments; and length of hospital stay. Sixty patients were randomly allocated equally between groups. The maximum pain score of patients receiving the pericapsular nerve group block was significantly lower than in the control group at all time‐points, with a median (IQR [range]) of 2.5 (2.0–3.7 [0–7]) vs. 5.5 (5.0–7.0 [2–8]) at 12 h; 3 (2.0–4.0 [0–7]) vs. 6 (5.0–6.0 [2–8]) at 24 h; and 2.0 (2.0–4.0 [0–5]) vs. 3.0 (2.0–4.7 [0–6]) at 48 h; all p < 0.001. Moreover, the pericapsular nerve group showed a significant reduction in opioid consumption, better range of hip motion and shorter time to ambulation. Although no significant difference in hospital length of stay was detected, our results suggest improved postoperative functional recovery following total hip arthroplasty in patients who received pericapsular nerve group block.